Amorphous nickel nanophases inducing ferromagnetism in equiatomic NiTi alloy. (December 2018) - Chellali, M.R.; Nandam, S.H.; Li, S.; Fawey, M.H.; Moreno-Pineda, E.; Velasco, L.; Boll, T.; Pastewka, L.; Kruk, R.; Gumbsch, P.; Hahn, H.
Abstract: Ni50 Ti50  nm-sized amorphous particles are prepared using inert-gas condensation followed by in situ compaction. Elemental segregation of Ni and Ti is observed in the consolidated nanostructured material. Amorphous, nearly pure Nickel (96%) nanophases form within the amorphous Ni50 Ti50 alloy. Combining atom probe tomography and scanning transmission electron microscopy with computer modelling, we explore the formation process of such amorphous nanophase structure. It is shown that the Ni rich amorphous phase in the consolidated nanostructured material is responsible for the ferromagnetic behavior of the sample whereas the rapidly quenched amorphous and crystalline samples with the same chemical composition (Ni50 Ti50 ) were found to be paramagnetic. Due to the high cooling rate obtained using the inert gas condensation technique, an exceptional control over the crystallization processes is possible, promoting the formation of various amorphous phases, which are not obtained by standard rapid quenching techniques. Our findings demonstrate the potential of amorphous metallic nanostructures as advanced technological materials, and useful magnetic compounds. Graphical abstract: Image 1